Modernist nowheres : politics and utopia in early modernist writing, 1900-1920 (Palgrave Macmillan, 2012)
"Modernist Nowheres explores connections in the Anglo-American sphere between early literary modernist cultures, politics, and utopia. Foregrounding such writers as Conrad, Lawrence and Wyndham Lewis, it presents a new reading of early modernism in which utopianism plays a defining role prior to, during and immediately after the First World War"--